Evidence of mood states in reptiles - Tatjana Hoehfurtner; Anna Wilkinson; Sophie A. Moszuti; Oliver H.P. Burman (Animal Cognition, 2025)
Abstract There is increasing evidence that non-human animals experience ‘free-floating’ mood states, but such evidence is lacking in reptiles, hindering the debate as to their affective capacity and with subsequent implications for welfare. Here, we investigated the presence of a mood state in a species of reptile, the red-footed tortoise (Chelonoidis carbonaria), using a spatial cognitive judgement bias task — an approach reliably used to determine background mood — alongside their behavioural response in anxiety tests. Our results showed that, as found in mammals and birds, individuals kept in appropriate conditions showed an optimistic mood, approaching ambiguous locations more rapidly when these were positioned closer to a rewarded location. This finding was reflected in associations between cognitive bias performance and behaviour in the concurrent anxiety tests, with more optimistic individuals showing less anxious behaviour in response to novelty. These findings significantly extend contemporary knowledge of the affective and cognitive capacity of reptiles and have important implications, not only for informing the management of reptiles but also for furthering our understanding of phylogenetic pathways of affective state.